(untitled) (Global Scientific Review, 2025)
The article examines and analyzes the concept of the "green economy" and its impact on the country’s economy, the significance, possibilities, basic principles, promising and priority areas of the "green" economy in the context of implementing the concept of sustainable development, the effectiveness of the application of the model of its future development, the main stages of a comprehensive assessment of "green" growth and effective environmental policy.